Edukasi digital marketing sebagai upaya peningkatan keterampilan digital masyarakat Pemagarsari (TEKMULOGI: Jurnal Pengabdian Masyarakat, 2026)
This study presents an innovative community-based digital marketing training program in Pemagarsari Village aimed at empowering rural housewives facing low digital literacy. The program introduces key digital marketing concepts, e-commerce, and cybersecurity, utilizing a pre-experimental one-group pre-test post-test design analyzed to empirically measure intervention effectiveness. Result demonstrated a substantial improvement in participants’ digital literacy, with average scores rising from 50 (pre-test) to 80 (post-test), and most participants showing newly acquired skills in basic e-commerce operations and business-focused social media use. These findings highlight the empirical contribution of structured training for building digital capacities among rural women and offer a scalable intervention model for similar communities. The main limitations of this study, small sample size and basic training module scope, suggest the need for follow-up research employing longitudinal approaches and ongoing digital mentoring to sustain transformation. Overall, this program provides a foundational step for accelerating the digital economic development of rural communities.